INTEGRATED REPORTING DISCLOSURE, BUSINESS COMPLEXITY AND FIRM VALUE - Seful Komar; Nurmala Ahmar; Dwi Prastowo Darminto (Faculty of Economics and Business, Universitas Pasundan, Bandung, Indonesia, 2020)
This study empirically investigates the effect of disclosure elements of integrated reporting on firm value. Business complexity is used as a moderating variable in the effect of integrated reporting on firm value. A total of 189 samples of manufacturing companies registered on the Indonesia Stock Exchange in 2015-2017 met the criteria using the purposive sampling method. A multiple linear regression analysis using SEM-PLS program is employed as a data analysis tool. The results showed that integrated reporting has significant effect on firm value. Business complexity moderates the relationship of disclosure integrated reporting to firm value. The better quality of information disclosure from element of integrated reporting increases investor confidence thereby increasing firm value.